KEBIJAKAN INVESTASI MASA PADEMI COVID-19 DI INDONESIA - Husnulwati, Sri; Yanuarsi, Susi (Solusi, 2021)
The Investment is all forms of investment activities, either by domestic investors or foreign investors to conduct business in the territory of the Republic of Indonesia. The basic policy on investment regulations is in line with one of the goals of forming a state government, namely, to advance the general welfare. During the Covid-19 pandemic in Indonesia, which has caused people's purchasing power to decline in consumption activities, it is necessary to encourage government spending and additional investment. Investment policies must make it easy for investors to invest in Indonesia. Law Number 11 of 2020 concerning Job Creation provides convenience in investing, especially in licensing issues. The Job Creation Law is expected to increase investment in Indonesia.